Financing of education for economic growth - Reifman, Lucille; Study Group in the Economics of Education (Paris : O. E. C. D. London, H.M.S.O., 1966)
The volume is devoted to the problems and principles of educational finance of the less developed area.
rpm 21/01/2019
Loans
Keywords: Education; Education